Pembelajaran Green Exercise Meningkatkan Kemampuan Fisik Motorik Kasar Anak Usia Dini - Maghfiroh Maghfiroh; Henni Anggaini; Rina Wijayanti (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to examine the implementation of Green Exercise learning in improving the gross motor skills of children aged 4–5 years at TK Plus Wahidiyah Poncokusumo. The method employed was Classroom Action Research (CAR) using the Kemmis and Taggart model, which consists of four stages: planning, action implementation, observation, and reflection. The research subjects comprised 11 children from Group A, consisting of 5 girls and 6 boys. Initial observations indicated that the average level of children’s gross motor skills was 36%. Following the implementation of Green Exercise learning, gradual improvements were observed. In Cycle 1, Meeting 1, the average level increased to 54% and further improved to 68% in Meeting 2. The improvement continued in Cycle 2, reaching an average of 80% in Meeting 1 and 90% in Meeting 2. These findings demonstrate that Green Exercise is effective in enhancing the gross motor skills of early childhood learners. Physical activities conducted in outdoor settings were proven to encourage children to be more active, confident, and to exhibit significant motor development.